rhBMP-2-loaded hydroxyapatite/beta-tricalcium phosphate microsphere/hydrogel composite promotes bone regeneration in a novel rat femoral nonunion model - Kitahara, Takayuki; Tateiwa, Daisuke; Hirai, Hiromasa; Ikuta, Masato; Furuichi, Takuya; Bun, Masayuki; Ukon, Yuichiro; Kanie, Yuya; Furuya, Masayuki; Fujimori, Takahito; Okada, Seiji; Kaito, Takashi (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Nonunion following fracture treatment remains a significant clinical challenge, adversely affecting the patient’s quality of life and imposing a substantial economic burden. The emergence of bone morphogenetic protein 2 (BMP-2) for bone regeneration represents a promising avenue, albeit limited by side effects such as inflammatory reactions primarily due to suboptimal drug delivery systems. This study focuses on NOVOSIS putty (NP), a novel biomaterial designed for the sustained release of BMP-2, aiming to mitigate these limitations and enhance bone healing. Objective: This research aimed to evaluate the effectiveness of NP, a hydroxyapatite granules/β-tricalcium phosphate hydrogel composite (HA/β-TCP/hydrogel), as a BMP-2 carrier for promoting bone regeneration in a new rat nonunion model of long bone. Methods: Using Sprague Dawley rats, a 2-mm silicone disk was interposed at the femoral fracture site, and intramedullary fixation with K-wire was performed to create a nonunion with a 2-mm bone defect. After 3 weeks, internal fixation with a plate, removal of the silicon disk, and refreshing the nonunion site were performed by implanting three different materials into the nonunion sites: allogenic iliac bone (IB), collagen sponge (CS) containing 10 μg of BMP-2, or NP containing 10 μg of BMP-2. Bone healing was evaluated weekly using micro-computed tomography (CT); ex vivo micro-Ct and histological evaluation were conducted at 6 weeks. Results: At 6 weeks, NP demonstrated a significantly higher bone union rate (76.5%) compared with the CS group (35.3%, p = 0.037), and the IB group (6.3%, p < 0.0001). Bone mineral density (BMD) and bone volume/tissue volume (BV/TV) were also significantly higher in the NP group compared with the CS group (BMD, p < 0.0001; BV/TV, p = 0.031). Histological analysis showed the fracture gap in the NP group was filled with more trabecular bone and less fibrous tissue compared with the CS group. Conclusion: The study confirms NP is a highly effective BMP-2 carrier, significantly improving bone union rates and new bone formation in nonunion fractures. The sustained release of BMP-2 from the hydrogel component reduced inflammatory responses and enhanced bone regeneration. NP can be a promising alternative to collagen-based BMP-2 delivery systems.